The relationship between adolescents' externalizing and internalizing symptoms and brain development over a period of three years - Jarvers, Irina; Kandsperger, Stephanie; Schleicher, Daniel; Ando, Ayaka; Resch, Franz; Koenig, Julian; Kaess, Michael; Brunner, Romuald (NeuroImage: Clinical, 2022)
Background - Adolescence is a crucial period for both brain maturation and the emergence of mental health disorders. Associations between brain morphology and internalizing/externalizing symptomatology have been identified in clinical or at-risk samples, but age-related developmental differences were rarely considered. The current study investigated the longitudinal relationship between internalizing/externalizing symptoms and brain development in the absence of psychiatric disorders during early and late adolescence. - Methods - 98 healthy adolescents within two cohorts (younger: 9 years, older: 12 years) participated in annual assessments for three years; a clinical assessment measuring their externalizing and internalizing symptoms (SDQ) and an MRI assessment measuring their brain volume and white matter microstructure, including fractional anisotropy (FA), mean diffusivity (MD) and average path length. - Results - Linear mixed effect models and cross-lagged panel models showed that larger subcortical gray matter volume predicted more externalizing symptoms in older adolescents whereas decreases of subcortical gray matter volume predicted more externalizing symptoms for younger adolescents. Additionally, longer average white matter path length predicted more externalizing symptoms for older adolescents, while decreases in cerebral white matter volume were predictive of more externalizing symptoms for younger adolescents. There were no predictive effects for internalizing symptoms, FA or MD. - Conclusions - Delays in subcortical brain maturation, in both early and late adolescence, are associated with increases in externalizing behavior which indicates a higher risk for psychopathology and warrants further investigations.
Gesehen am 15.12.2022